Resin films, laminates, coverlay films, resin-coated copper foils, metal-clad laminates, circuit boards and multilayer circuit boards
A polyimide-based resin film with specific tetracarboxylic acid and diamine components addresses the issue of increasing dielectric loss with frequency, ensuring low transmission loss across the 10GHz to 40GHz band, suitable for 5G communication.
Patent Information
- Application Number
- JP2021058969
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-03-31
Smart Images

Figure 0007621161000007 
Figure 0007621161000008 
Figure 0007621161000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin film, a laminate, a coverlay film, a resin-coated copper foil, a metal-clad laminate, a circuit board, and a multilayer circuit board that are useful as materials for electronic components. [Background technology]
[0002] In recent years, with the progress of miniaturization, weight saving, and space saving of electronic devices, there is an increasing demand for flexible printed circuits (FPCs) that are thin, lightweight, flexible, and have excellent durability even when repeatedly bent. Because FPCs allow three-dimensional and high-density mounting even in a limited space, their applications are expanding to include wiring for moving parts of electronic devices such as HDDs, DVDs, and smartphones, as well as components such as cables and connectors.
[0003] One embodiment of FPC is a structure in which a circuit pattern is formed on a polyimide film having excellent heat resistance and flexibility, and a coverlay film having an adhesive layer is laminated on the surface of the polyimide film. Polyimide is also used as the material for the adhesive layer of the coverlay film having such a structure. For example, Patent Document 1 proposes that a crosslinked polyimide obtained by reacting a polyimide made of a dimer diamine derived from a dimer acid with an amino compound having at least two primary amino groups as functional groups is applied to the adhesive layer of the coverlay film. Here, the dimer acid is a dimerized fatty acid obtained by Diels-Alder reaction using natural fatty acids such as soybean oil fatty acid, tall oil fatty acid, rapeseed oil fatty acid, and oleic acid, linoleic acid, linolenic acid, erucic acid, and the like, which are refined from these, as raw materials, and it is known that a polybasic acid compound derived from a dimer acid is obtained as a composition of raw fatty acid and trimerized or higher fatty acid (for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-1730 A [Patent Document 2] JP 2017-137375 A Summary of the Invention [Problem to be solved by the invention]
[0005] Currently, with the progress of high performance of devices, it is necessary to deal with the high frequency of transmission signals. When transmitting high frequency signals, if the transmission loss in the transmission path is large, inconveniences such as loss of electrical signals and long delay time of signals occur. For FPCs, it is important to effectively reduce the transmission loss in both frequency bands of Sub6 (e.g., 3.6 GHz to less than 6 GHz) and millimeter wave (e.g., 28 GHz to 300 GHz) in order to support 5G (fifth generation mobile communication system). Therefore, further improvement of the dielectric properties is also required for resin films as constituent materials of FPCs, and it is considered preferable that the dielectric loss tangent, which is closely related to the transmission loss, shows a low value below a certain value in the entire frequency range of the GHz band (meaning, for example, 1 to 50 GHz), especially the frequency band of 10 GHz to 40 GHz. However, since the dielectric loss tangent of conventional resin films using polyimide shows a tendency to increase with increasing frequency (frequency dependency), improvement in this respect has been strongly demanded.
[0006] Therefore, an object of the present invention is to provide a resin film that exhibits a low dielectric tangent over the entire frequency band from 10 GHz to 40 GHz and is capable of more effectively reducing the transmission loss of high-frequency signals. [Means for solving the problem]
[0007] As a result of extensive research, the inventors have found that resin films using polyimides derived from dimer diamine have no frequency dependence of dielectric tangent or tend to exhibit a decrease in dielectric tangent inversely proportional to an increase in frequency, thereby completing the present invention. That is, the resin film of the present invention is a resin film containing a polyimide as a resin component, the polyimide containing a tetracarboxylic acid residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and containing 30 mol% or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid residues of a dimer acid are substituted with a primary aminomethyl group or an amino group, relative to the total diamine residues. The resin film of the present invention has a dielectric loss tangent (Tanδ1) at 10 GHz and a dielectric loss tangent (Tanδ2) at 28 GHz measured by a split cylinder resonator (SCDR) after 24 hours of humidity control under constant temperature and humidity conditions (normal state) of 23°C and 50% RH, both of which are less than 0.0025, and the ratio of Tanδ2 to Tanδ1 (Tanδ2 / Tanδ1) is 0.5 or more and 1.0 or less.
[0008] In the resin film of the present invention, the absolute value of the difference between Tan δ1 and Tan δ2 may be 0.0010 or less.
[0009] The resin film of the present invention may have a dielectric loss tangent (Tan δ3) of less than 0.0025 at 40 GHz measured with a split cylinder resonator (SCDR) after being conditioned for 24 hours under constant temperature and humidity conditions (normal state) of 23° C. and 50% RH.
[0010] In the resin film of the present invention, the ratio of Tan δ3 to Tan δ1 (Tan δ3 / Tan δ1) may be 0.5 or more and 1.0 or less.
[0011] In the resin film of the present invention, the absolute value of the difference between Tan δ1 and Tan δ3 may be less than 0.0011.
[0012] The resin film of the present invention may contain a crosslinked polyimide obtained by crosslinking the polyimide through an imine bond.
[0013] The laminate of the present invention is a laminate having a substrate and an adhesive layer laminated on at least one surface of the substrate, the adhesive layer being made of any of the resin films described above.
[0014] The coverlay film of the present invention is a coverlay film having a coverlay film material layer and an adhesive layer laminated on the coverlay film material layer, and the adhesive layer is made of any of the resin films described above.
[0015] The resin-coated copper foil of the present invention is a resin-coated copper foil comprising an adhesive layer and a copper foil laminated together, the adhesive layer being made of any one of the resin films described above.
[0016] The metal-clad laminate of a first aspect of the present invention is a metal-clad laminate having an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, at least one of the insulating resin layers being made of any of the resin films described above.
[0017] A metal-clad laminate according to a second aspect of the present invention is a metal-clad laminate having an insulating resin layer, an adhesive layer laminated on at least one surface of the insulating resin layer, and a metal layer laminated on the insulating resin layer via the adhesive layer, wherein the adhesive layer is made of any of the resin films described above.
[0018] A metal-clad laminate according to a third aspect of the present invention includes a first single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on at least one surface of the first metal layer; a second single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on at least one surface of the second metal layer; An adhesive layer is arranged so as to abut against the first insulating resin layer and the second insulating resin layer, and is laminated between the first single-sided metal-clad laminate and the second single-sided metal-clad laminate, The adhesive layer is made of any one of the resin films described above.
[0019] A metal-clad laminate according to a fourth aspect of the present invention comprises a single-sided metal-clad laminate having an insulating resin layer and a metal layer laminated on one side of the insulating resin layer, and an adhesive layer laminated on the other side of the insulating resin layer, wherein the adhesive layer is made of any of the resin films described above.
[0020] A circuit board according to a first aspect of the present invention is obtained by wiring the metal layer of the metal-clad laminate.
[0021] A circuit board according to a second aspect of the present invention is a circuit board comprising a first base material, a wiring layer laminated on at least one surface of the first base material, and an adhesive layer laminated on the surface of the first base material facing the wiring layer so as to cover the wiring layer, wherein the adhesive layer is made of any of the resin films described above.
[0022] A circuit board according to a third aspect of the present invention is a circuit board comprising a first base material, a wiring layer laminated on at least one surface of the first base material, an adhesive layer laminated on the surface of the first base material facing the wiring layer so as to cover the wiring layer, and a second base material laminated on the surface of the adhesive layer opposite the first base material, wherein the adhesive layer is made of any of the resin films described above.
[0023] A circuit board according to a fourth aspect of the present invention is a circuit board comprising a first base material, an adhesive layer laminated on at least one surface of the first base material, a second base material laminated on a surface of the adhesive layer opposite the first base material, and wiring layers laminated on each of the surfaces of the first base material and the second base material opposite the adhesive layer, wherein the adhesive layer is made of any of the resin films described above.
[0024] The multilayer circuit board of the present invention is a multilayer circuit board including a laminate including a plurality of laminated insulating resin layers, and at least one wiring layer embedded in the laminate, At least one of the insulating resin layers is formed of an adhesive layer having adhesiveness and covering the wiring layer, and the adhesive layer is made of any of the resin films described above. Effect of the Invention
[0025] The resin film of the present invention uses a polyimide made from dimer diamine as a raw material, and therefore not only exhibits a low dielectric tangent over the entire frequency band of 10 GHz to 40 GHz, but also shows a tendency that the dielectric tangent is constant or even decreases with increasing frequency. Therefore, when the resin film of the present invention is applied to a circuit board or the like that transmits high-frequency signals in frequency bands including both Sub6 and millimeter waves, it is possible to effectively reduce transmission loss, and is very advantageous in application to 5G-compatible communication devices. [Brief description of the drawings]
[0026] [Figure 1] 1 is a schematic diagram showing a cross-sectional configuration of a laminate according to an embodiment of the present invention. [Diagram 2] 1 is a schematic diagram showing a cross-sectional configuration of a metal-clad laminate according to one embodiment of the present invention. [Diagram 3] FIG. 4 is a schematic diagram showing a cross-sectional configuration of a metal-clad laminate according to another embodiment of the present invention. [Figure 4] FIG. 4 is a schematic diagram showing a cross-sectional configuration of a metal-clad laminate according to yet another embodiment of the present invention. [Diagram 5] 1 is a schematic diagram showing a cross-sectional configuration of a circuit board according to an embodiment of the present invention; [Figure 6] FIG. 13 is a schematic diagram showing a cross-sectional configuration of a circuit board according to another embodiment of the present invention. [Figure 7] FIG. 13 is a schematic diagram showing a cross-sectional configuration of a circuit board according to still another embodiment of the present invention. [Figure 8] 1 is a schematic diagram showing a cross-sectional configuration of a multilayer circuit board according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] An embodiment of the present invention will be described with reference to the drawings as appropriate. A resin film according to one embodiment of the present invention is a resin film containing polyimide as a resin component. The polyimide used in this embodiment is a polyimide having adhesive properties (hereinafter, may be referred to as "adhesive polyimide"). In the following, first, the adhesive polyimide will be described, and then the resin film will be described.
[0028] [Adhesive polyimide] The adhesive polyimide contains a tetracarboxylic acid residue derived from a tetracarboxylic acid anhydride component and a diamine residue derived from a diamine component. In the present invention, the "tetracarboxylic acid residue" refers to a tetravalent group derived from a tetracarboxylic acid dianhydride, and the "diamine residue" refers to a divalent group derived from a diamine compound. When the raw materials, tetracarboxylic acid dianhydride and diamine compound, are reacted in approximately equal moles, the types and molar ratios of the tetracarboxylic acid residue and diamine residue contained in the polyimide can be made to correspond approximately to the types and molar ratios of the raw materials. In the present invention, the term "polyimide" refers to a resin made of a polymer having an imide group in the molecular structure, such as polyimide, polyamideimide, polyetherimide, polyesterimide, polysiloxaneimide, polybenzimidazoleimide, etc.
[0029] (acid anhydride) The adhesive polyimide may be made of any tetracarboxylic dianhydride generally used in thermoplastic polyimides as a raw material, without any particular limitations. However, it is preferable to use a raw material containing 90 mol % or more of tetracarboxylic dianhydrides represented by the following general formula (1) and / or (2) in total relative to the total tetracarboxylic dianhydride components. In other words, the adhesive polyimide preferably contains 90 mol % or more of tetracarboxylic dianhydrides derived from the following general formula (1) and / or (2) in total relative to the total tetracarboxylic dianhydride residues. By containing 90 mol % or more of tetracarboxylic dianhydrides derived from the following general formula (1) and / or (2) in total relative to the total tetracarboxylic dianhydride residues, it is preferable that the adhesive polyimide is easily compatible with flexibility and heat resistance. If the total amount of tetracarboxylic dianhydrides derived from the following general formula (1) and / or (2) is less than 90 mol %, the adhesive polyimide tends to have a low solvent solubility.
[0030] [ka]
[0031] In general formula (1), X represents a single bond or a divalent group selected from the following formulas, and in general formula (2), the cyclic moiety represented by Y represents the formation of a cyclic saturated hydrocarbon group selected from a 4-membered ring, a 5-membered ring, a 6-membered ring, a 7-membered ring, or an 8-membered ring.
[0032] [ka]
[0033] In the above formula, Z represents -C6H4-, -(CH2)n-, or -CH2-CH(-OC(=O)-CH3)-CH2-, where n represents an integer of 1 to 20.
[0034] Examples of the tetracarboxylic dianhydride represented by the above general formula (1) include 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic monoester acid anhydride) (TAHQ), ethylene glycol bisanhydrotrimellitate (TMEG), etc. Among these, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) is particularly preferred. When BTDA is used, the carbonyl group (ketone group) contributes to adhesion, so that the adhesion of the adhesive polyimide can be improved. In addition, the ketone group present in the molecular skeleton of BTDA may react with the amino group of an amino compound for crosslinking, which will be described later, to form a C=N bond, which is likely to exhibit the effect of improving heat resistance. From this viewpoint, it is preferable that the tetracarboxylic acid residue derived from BTDA is contained in an amount of preferably 50 mol % or more, more preferably 60 mol % or more, of the total tetracarboxylic acid residues.
[0035] Examples of the tetracarboxylic dianhydride represented by the general formula (2) include 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,2,4,5-cycloheptane tetracarboxylic dianhydride, and 1,2,5,6-cyclooctane tetracarboxylic dianhydride.
[0036] The adhesive polyimide may contain tetracarboxylic acid residues derived from acid anhydrides other than the tetracarboxylic dianhydrides represented by the above general formulas (1) and (2), as long as the effects of the invention are not impaired.Such a tetracarboxylic acid residue is not particularly limited, and examples thereof include pyromellitic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'- or 2,3,3',4'-benzophenonetetracarboxylic dianhydride, 2,3',3,4'-diphenylethertetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, 3,3'',4,4''-, 2,3,3'',4''- or 2,2'',3,3''-p-terphenyltetracarboxylic dianhydride, 2,3',3,4''- ... ,2-Bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)methane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3- or 3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-, 1,2,6,7- or 1,2,9,10-phenanthrene-tetracarboxylic acid dianhydride, 2,3,6,7-anthracene tetracarboxylic acid dianhydride, 2,2-bis(3,4-dicarboxyphenyl) ) tetrafluoropropane dianhydride, 1,2,5,6-naphthalene tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, 2,6- or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloronaphthalene-1,4,5,8-(or 2, 3,6,7-tetracarboxylic acid dianhydride, 2,3,8,9-, 3,4,9,10-, 4,5,10,11- or 5,6,11,12-perylene-tetracarboxylic acid dianhydride, pyrazine-2,3,5,6-tetracarboxylic acid dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic acid dianhydride, thiophene-2,3,4,5-tetracarboxylic acid dianhydride, 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride and other aromatic tetracarboxylic acid dianhydrides.
[0037] (Diamine) The adhesive polyimide may use, without any particular limitation, any diamine compound generally used in thermoplastic polyimides as a raw material, but a raw material containing 30 mol % or more of a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine components, is used. In other words, the adhesive polyimide contains 30 mol % or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine residues. The relative dielectric constant and dielectric loss tangent of the polyimide can be reduced by setting the content of the diamine residue derived from the dimer diamine composition to 30 mol% or more, preferably 40 mol% or more, more preferably within the range of 70 to 99 mol%, and even more preferably within the range of 80 to 95 mol% relative to the total diamine residues. If the content of the diamine residue derived from the dimer diamine composition is less than 30 mol%, the relative dielectric constant and dielectric loss tangent tend to increase due to the relatively increased polar groups contained in the polyimide. In addition, by containing the diamine residue derived from the dimer diamine composition in the above amount, the glass transition temperature of the polyimide can be lowered (lowered Tg), thereby improving the thermocompression bonding properties, and the internal stress can be alleviated due to the lowered elastic modulus.
[0038] The dimer diamine composition is a refined product containing the following component (a) as a main component with the amounts of components (b) and (c) being controlled.
[0039] (a) dimer diamine; The dimer diamine of the component (a) means a diamine in which two terminal carboxylic acid groups (-COOH) of a dimer acid are replaced by primary aminomethyl groups (-CH2-NH2) or amino groups (-NH2). Dimer acid is a known dibasic acid obtained by intermolecular polymerization of unsaturated fatty acids, and its industrial production process is almost standardized in the industry, and is obtained by dimerizing unsaturated fatty acids having 11 to 22 carbon atoms using a clay catalyst or the like. Industrially obtained dimer acid is mainly composed of a dibasic acid having 36 carbon atoms obtained by dimerizing unsaturated fatty acids having 18 carbon atoms, such as oleic acid, linoleic acid, and linolenic acid, but contains any amount of monomer acid (having 18 carbon atoms), trimer acid (having 54 carbon atoms), and other polymerized fatty acids having 20 to 54 carbon atoms depending on the degree of purification. In addition, although double bonds remain after the dimerization reaction, in the present invention, those which have been further subjected to a hydrogenation reaction to reduce the degree of unsaturation are also included in the dimer acid. The dimer diamine of component (a) can be defined as a diamine compound obtained by substituting the terminal carboxylic acid group of a dibasic acid compound having 18 to 54 carbon atoms, preferably 22 to 44 carbon atoms, with a primary aminomethyl group or an amino group.
[0040] As a feature of dimer diamine, it is possible to impart characteristics derived from the skeleton of dimer acid. That is, since dimer diamine is an aliphatic macromolecule with a molecular weight of about 560 to 620, it is possible to increase the molar volume of the molecule and relatively reduce the polar group of the polyimide. It is considered that such a feature of dimer acid type diamine contributes to improving the dielectric properties by reducing the dielectric constant and dielectric loss tangent while suppressing the deterioration of the heat resistance of the polyimide. In addition, since it has two freely moving hydrophobic chains with 7 to 9 carbon atoms and two chain-like aliphatic amino groups with a length close to 18 carbon atoms, it is not only possible to impart flexibility to the polyimide, but also possible to make the polyimide have an asymmetric chemical structure or a non-planar chemical structure, and therefore it is considered that it is possible to reduce the dielectric constant of the polyimide.
[0041] The dimer diamine composition is preferably used in which the dimer diamine content of the (a) component is increased to 96% by weight or more, preferably 97% by weight or more, more preferably 98% by weight or more by a purification method such as molecular distillation. By making the dimer diamine content of the (a) component 96% by weight or more, the spread of the molecular weight distribution of the polyimide can be suppressed. If technically possible, it is best that all (100% by weight) of the dimer diamine composition is composed of the dimer diamine of the (a) component. The dimer diamine composition may contain a dimer diamine having a 6-membered aromatic ring as a molecular skeleton. In the adhesive polyimide, the ratio of aromatic monomers directly bonded to the imide bond site is controlled, but in the dimer diamine having a 6-membered aromatic ring, the 6-membered aromatic ring is an imide bond via an aliphatic chain having a length of 7 carbon atoms or more, so the 6-membered aromatic ring in the adhesive polyimide is not controlled. Therefore, the 6-membered aromatic ring derived from the dimer diamine is excluded from the content of carbon atoms derived from the 6-membered aromatic ring in the adhesive polyimide. The proportion of aromatic rings derived from dimer diamine is preferably 20 moles or less per mole of amino groups, as quantified by 1H-NMR.
[0042] (b) a monoamine compound obtained by substituting a terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group; The monobasic acid compound having 10 to 40 carbon atoms is a mixture of a monobasic unsaturated fatty acid having 10 to 20 carbon atoms derived from the raw material of dimer acid, and a monobasic acid compound having 21 to 40 carbon atoms which is a by-product during the production of dimer acid. The monoamine compound is obtained by substituting the terminal carboxylic acid group of these monobasic acid compounds with a primary aminomethyl group or an amino group.
[0043] The monoamine compound (b) is a component that suppresses an increase in the molecular weight of the polyimide. During polymerization of the polyamic acid or polyimide, the monofunctional amino group of the monoamine compound reacts with the terminal acid anhydride group of the polyamic acid or polyimide to cap the terminal acid anhydride group, thereby suppressing an increase in the molecular weight of the polyamic acid or polyimide.
[0044] (c) an amine compound obtained by substituting a terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine); The polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms is a polybasic acid compound mainly composed of a tribasic acid compound having 41 to 80 carbon atoms, which is a by-product during the production of dimer acid. It may also contain a polymerized fatty acid other than dimer acid having 41 to 80 carbon atoms. The amine compound is obtained by substituting the terminal carboxylic acid group of these polybasic acid compounds with a primary aminomethyl group or an amino group.
[0045] The amine compound (c) is a component that promotes an increase in the molecular weight of the polyimide. The trifunctional or higher amino group, the main component of which is a triamine derived from a trimer acid, reacts with the terminal acid anhydride group of the polyamic acid or polyimide, rapidly increasing the molecular weight of the polyimide. In addition, amine compounds derived from polymerized fatty acids other than dimer acids having 41 to 80 carbon atoms also increase the molecular weight of the polyimide, causing gelation of the polyamic acid or polyimide.
[0046] When each component is quantified by measurement using gel permeation chromatography (GPC), in order to easily confirm the peak start, peak top, and peak end of each component of the dimer diamine composition, a sample of the dimer diamine composition treated with acetic anhydride and pyridine is used, and cyclohexanone is used as an internal standard. Using the sample thus prepared, each component is quantified by the area percentage of the GPC chromatogram. The peak start and peak end of each component are the minimum values of each peak curve, and the area percentage of the chromatogram can be calculated based on this.
[0047] In addition, the dimer diamine composition has a total area percentage of components (b) and (c) of 4% or less, preferably less than 4%, in a chromatogram obtained by GPC measurement. By keeping the total area percentage of components (b) and (c) at 4% or less, the broadening of the molecular weight distribution of the polyimide can be suppressed.
[0048] The area percentage of the chromatogram of the (b) component is preferably 3% or less, more preferably 2% or less, and even more preferably 1% or less. By setting it in such a range, it is possible to suppress the decrease in the molecular weight of the polyimide, and further to widen the range of the molar ratio of the tetracarboxylic anhydride component and the diamine component. It is not necessary for the (b) component to be contained in the dimer diamine composition.
[0049] The area percentage of the chromatogram of component (c) is 2% or less, preferably 1.8% or less, and more preferably 1.5% or less. By setting it in such a range, a sudden increase in the molecular weight of the polyimide can be suppressed, and further, an increase in the dielectric tangent of the resin film over a wide frequency range can be suppressed. Note that component (c) does not have to be contained in the dimer diamine composition.
[0050] In addition, when the ratio (b / c) of the area percentages of the chromatograms of the components (b) and (c) is 1 or more, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably 0.97 or more and less than 1.0. By setting such a molar ratio, it becomes easier to control the molecular weight of the polyimide.
[0051] Furthermore, when the ratio (b / c) of the area percentages of the components (b) and (c) in the chromatograms is less than 1, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably 0.97 or more and 1.1 or less. By setting such a molar ratio, it becomes easier to control the molecular weight of the polyimide.
[0052] The dimer diamine composition is available as a commercially available product, and is preferably purified to reduce the amount of components other than the dimer diamine of the component (a), for example, the amount of the component (a) is preferably 96% by area or more. The purification method is not particularly limited, but known methods such as distillation and precipitation purification are suitable. Examples of commercially available dimer diamine compositions include PRIAMINE 1073 (trade name), PRIAMINE 1074 (trade name), and PRIAMINE 1075 (trade name) manufactured by Croda Japan.
[0053] The adhesive polyimide may contain a diamine residue derived from a diamine component other than the above. As such a diamine residue, for example, a diamine residue derived from a diamine compound having a fluorene skeleton such as bisanilinefluorene (BAFL), 9,9-bis(3-methyl-4-aminophenyl)fluorene, 9,9-bis(3-fluoro-4-aminophenyl)fluorene, or 9,9-bis[4-(aminophenoxy)phenyl]fluorene, or a diamine residue derived from a diamine compound represented by the following general formulas (B1) to (B7) is preferable. In particular, a diamine residue derived from a diamine compound having a fluorene skeleton, such as BAFL, contains four aromatic rings, and therefore can be advantageously used for the purpose of adjusting the aromatic ring concentration.
[0054] [ka]
[0055] In formulas (B1) to (B7), R1 independently represents a monovalent hydrocarbon group or alkoxy group having 1 to 6 carbon atoms, linking group A independently represents a divalent group selected from -O-, -S-, -CO-, -SO-, -SO2-, -COO-, -CH2-, -C(CH3)2-, -NH-, or -CONH-, and n1 independently represents an integer of 0 to 4. However, formula (B3) excluding those that overlap with formula (B2), and formula (B5) excluding those that overlap with formula (B4). Here, "independently" means that in one or more of the above formulas (B1) to (B7), multiple linking groups A, multiple R1s, or multiple n1s may be the same or different. In the above formulas (B1) to (B7), the hydrogen atoms in the two terminal amino groups may be substituted, for example, -NR2R3 (wherein R2 and R3 independently represent any substituent such as an alkyl group).
[0056] The diamine represented by formula (B1) (hereinafter, sometimes referred to as "diamine (B1)") is an aromatic diamine having two benzene rings. In this diamine (B1), since at least one amino group directly bonded to the benzene ring and the divalent linking group A are at the meta position, the degree of freedom of the polyimide molecular chain is increased, resulting in high flexibility, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B1), the thermoplasticity of the polyimide is increased. Here, the linking group A is preferably -O-, -CH2-, -C(CH3)2-, -CO-, -SO2-, or -S-.
[0057] Examples of the diamine (B1) include 3,3'-diaminodiphenylmethane, 3,3'-diaminodiphenylpropane, 3,3'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylpropane, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminobenzophenone, and (3,3'-bisamino)diphenylamine.
[0058] The diamine represented by formula (B2) (hereinafter sometimes referred to as "diamine (B2)") is an aromatic diamine having three benzene rings. In this diamine (B2), the amino group directly bonded to at least one benzene ring and the divalent linking group A are at the meta position, so that the degree of freedom of the polyimide molecular chain is increased and the polyimide molecular chain has high flexibility, which is thought to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B2), the thermoplasticity of the polyimide is increased. Here, the linking group A is preferably -O-.
[0059] Examples of the diamine (B2) include 1,4-bis(3-aminophenoxy)benzene, 3-[4-(4-aminophenoxy)phenoxy]benzeneamine, and 3-[3-(4-aminophenoxy)phenoxy]benzeneamine.
[0060] The diamine represented by formula (B3) (hereinafter, sometimes referred to as "diamine (B3)") is an aromatic diamine having three benzene rings. In this diamine (B3), two divalent linking groups A directly bonded to one benzene ring are in meta positions with respect to each other, so that the degree of freedom of the polyimide molecular chain is increased and the polyimide molecular chain has high flexibility, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B3), the thermoplasticity of the polyimide is increased. Here, as the linking group A, -O- is preferable.
[0061] Examples of diamine (B3) include 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (APB), 4,4'-[2-methyl-(1,3-phenylene)bisoxy]bisaniline, 4,4'-[4-methyl-(1,3-phenylene)bisoxy]bisaniline, and 4,4'-[5-methyl-(1,3-phenylene)bisoxy]bisaniline.
[0062] The diamine represented by formula (B4) (hereinafter, sometimes referred to as "diamine (B4)") is an aromatic diamine having four benzene rings. This diamine (B4) has high flexibility because at least one amino group directly bonded to the benzene ring and the divalent linking group A are at the meta position, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, the use of diamine (B4) enhances the thermoplasticity of the polyimide. Here, the linking group A is preferably -O-, -CH2-, -C(CH3)2-, -SO2-, -CO-, or -CONH-.
[0063] Examples of the diamine (B4) include bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)]benzophenone, and bis[4,4'-(3-aminophenoxy)]benzanilide.
[0064] The diamine represented by formula (B5) (hereinafter sometimes referred to as "diamine (B5)") is an aromatic diamine having four benzene rings. In this diamine (B5), two divalent linking groups A directly bonded to at least one benzene ring are mutually at meta positions, so that the degree of freedom of the polyimide molecular chain is increased and the polyimide molecular chain has high flexibility, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B5), the thermoplasticity of the polyimide is increased. Here, as the linking group A, -O- is preferable.
[0065] Examples of the diamine (B5) include 4-[3-[4-(4-aminophenoxy)phenoxy]phenoxy]aniline, 4,4'-[oxybis(3,1-phenyleneoxy)]bisaniline, and the like.
[0066] The diamine represented by formula (B6) (hereinafter sometimes referred to as "diamine (B6)") is an aromatic diamine having four benzene rings. This diamine (B6) has high flexibility due to having at least two ether bonds, and is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, the use of diamine (B6) enhances the thermoplasticity of the polyimide. Here, the linking group A is preferably -C(CH3)2-, -O-, -SO2-, or -CO-.
[0067] Examples of diamines (B6) include 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), bis[4-(4-aminophenoxy)phenyl]ether (BAPE), bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), and bis[4-(4-aminophenoxy)phenyl]ketone (BAPK).
[0068] The diamine represented by formula (B7) (hereinafter sometimes referred to as "diamine (B7)") is an aromatic diamine having four benzene rings. This diamine (B7) has a highly flexible divalent linking group A on both sides of the diphenyl skeleton, which is believed to contribute to improving the flexibility of the polyimide molecular chain. Therefore, the use of diamine (B7) enhances the thermoplasticity of the polyimide. Here, the linking group A is preferably -O-.
[0069] Examples of the diamine (B7) include bis[4-(3-aminophenoxy)]biphenyl, bis[4-(4-aminophenoxy)]biphenyl, and the like.
[0070] The adhesive polyimide may contain diamine residues derived from a diamine compound having a fluorene skeleton and at least one diamine compound selected from diamines (B1) to (B7) in a total amount of 70 mol % or less, preferably 60 mol % or less, more preferably in the range of 1 to 30 mol %, and even more preferably in the range of 5 to 20 mol %, based on the total diamine residues. The diamine compound having a fluorene skeleton is effective for adjusting the aromatic ring concentration, and diamines (B1) to (B7) have a molecular structure with flexibility, so that by using at least one diamine compound selected from these in an amount within the above range, the flexibility of the polyimide molecular chain can be improved and thermoplasticity can be imparted.
[0071] The adhesive polyimide may further contain diamine residues derived from diamine compounds other than those mentioned above, provided that the effect of the invention is not impaired.
[0072] The adhesive polyimide can be produced by reacting the above-mentioned acid anhydride component and diamine component in a solvent, generating polyamic acid, and then heating to close the ring. For example, the acid anhydride component and diamine component are dissolved in an organic solvent in approximately equimolar amounts, and the mixture is stirred at a temperature in the range of 0 to 100°C for 30 minutes to 24 hours to cause a polymerization reaction, thereby obtaining polyamic acid, which is a precursor of polyimide. In the reaction, the reaction components are dissolved in the organic solvent so that the generated precursor is in the range of 5 to 50% by weight, preferably in the range of 10 to 40% by weight. Examples of organic solvents used in the polymerization reaction include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexane, dioxane, tetrahydrofuran, diglyme, triglyme, methanol, ethanol, benzyl alcohol, and cresol. Two or more of these solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. The amount of such an organic solvent is not particularly limited, but it is preferable to adjust the amount so that the concentration of the polyamic acid solution obtained by the polymerization reaction is about 5 to 50% by weight.
[0073] The synthesized polyamic acid is usually advantageously used as a solution in a reaction solvent, but it can be concentrated, diluted, or replaced with another organic solvent if necessary. Polyamic acid is also advantageously used because it generally has excellent solubility in solvents. The viscosity of the polyamic acid solution is preferably within the range of 500 mPa·s to 100,000 mPa·s. If it is outside this range, defects such as uneven thickness and streaks are likely to occur in the film during coating using a coater or the like.
[0074] The method for imidizing polyamic acid to form polyimide is not particularly limited, and for example, a heat treatment in which the polyamic acid is heated in the above-mentioned solvent at a temperature in the range of 80 to 400° C. for 1 to 24 hours is preferably used. The temperature may be constant, or the temperature may be changed during the process.
[0075] In the adhesive polyimide, by selecting the types of the acid anhydride component and the diamine component, or by selecting the molar ratio of each when two or more types of acid anhydride components or diamine components are used, it is possible to control physical properties such as dielectric properties, thermal expansion coefficient, tensile modulus, glass transition temperature, etc. When the adhesive polyimide has a plurality of structural units, they may be present as blocks or randomly, but are preferably present randomly.
[0076] The imide group concentration of the adhesive polyimide is preferably 22% by weight or less, more preferably 20% by weight or less. Here, "imide group concentration" means the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire polyimide structure. If the imide group concentration exceeds 22% by weight, the molecular weight of the resin itself decreases, and the low moisture absorption property deteriorates due to the increase in polar groups, and Tg and elastic modulus increase.
[0077] The adhesive polyimide is most preferably a completely imidized structure. However, a part of the polyimide may be an amic acid. The imidization rate can be determined by measuring the infrared absorption spectrum of the polyimide thin film by a single reflection ATR method using a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1015 cm -1 Based on the benzene ring absorber near 1780cm -1 It can be calculated from the absorbance of the C=O stretching derived from the imide group.
[0078] (Crosslinking of adhesive polyimide) When the adhesive polyimide has a ketone group, the ketone group and the amino group of an amino compound having at least two primary amino groups as functional groups (hereinafter, sometimes referred to as "amino compound for crosslinking") are reacted to form a C=N bond, thereby forming a crosslinked structure. A polyimide having such a crosslinked structure (hereinafter, sometimes referred to as "crosslinked polyimide") is an application example of an adhesive polyimide and is a preferred embodiment. Since the weight average molecular weight varies greatly due to crosslinking, it is sufficient that the adhesive polyimide before crosslinking satisfies the weight average molecular weight described below, and the crosslinked polyimide does not have to satisfy the weight average molecular weight described below. In addition, a polyimide composition obtained by blending a crosslinking agent with an adhesive polyimide having a ketone group is another application example of an adhesive polyimide and is a preferred embodiment. The heat resistance of the adhesive polyimide can be improved by forming a crosslinked structure. A preferred example of a tetracarboxylic dianhydride for forming an adhesive polyimide having a ketone group is 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), and a preferred example of a diamine compound is an aromatic diamine such as 4,4'-bis(3-aminophenoxy)benzophenone (BABP) or 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene (BABB).
[0079] For the purpose of forming a crosslinked structure, it is particularly preferred to react a crosslinking amino compound with the above adhesive polyimide containing BTDA residues derived from BTDA in an amount of preferably 50 mol % or more, more preferably 60 mol % or more, based on the total tetracarboxylic acid residues. In the present invention, the term "BTDA residue" refers to a tetravalent group derived from BTDA.
[0080] Examples of the amino compound for forming a crosslink include (I) a dihydrazide compound, (II) an aromatic diamine, and (III) an aliphatic amine. Among these, a dihydrazide compound is preferred. Aliphatic amines other than dihydrazide compounds are likely to form a crosslinked structure even at room temperature, which raises concerns about the storage stability of the varnish, while aromatic diamines require high temperatures to form a crosslinked structure. In this way, when a dihydrazide compound is used, it is possible to achieve both the storage stability of the varnish and a shortened curing time. Examples of the dihydrazide compound include oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglyceryl ester dihydrazide, ... Preferred are dihydrazide compounds such as cholic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoic acid dihydrazide, 4,4-bisbenzene dihydrazide, 1,4-naphthoic acid dihydrazide, 2,6-pyridine diacid dihydrazide, itaconic acid dihydrazide, etc. The above dihydrazide compounds may be used alone or in combination of two or more.
[0081] In addition, the above amino compounds, such as (I) dihydrazide compounds, (II) aromatic diamines, and (III) aliphatic amines, can also be used in combination of two or more kinds beyond categories, such as a combination of (I) and (II), a combination of (I) and (III), or a combination of (I), (II) and (III).
[0082] In addition, from the viewpoint of making the network structure formed by the crosslinking by the crosslinking amino compound denser, the crosslinking amino compound used in the present invention preferably has a molecular weight (weight average molecular weight when the crosslinking amino compound is an oligomer) of 5,000 or less, more preferably 90 to 2,000, and even more preferably 100 to 1,500. Among these, crosslinking amino compounds having a molecular weight of 100 to 1,000 are particularly preferred. When the molecular weight of the crosslinking amino compound is less than 90, only one amino group of the crosslinking amino compound forms a C=N bond with a ketone group of the adhesive polyimide, and the periphery of the remaining amino group becomes three-dimensionally bulky, so that the remaining amino group tends to have difficulty in forming a C=N bond.
[0083] When crosslinking the ketone group in the adhesive polyimide with the crosslinking amino compound, the crosslinking amino compound is added to a resin solution containing the adhesive polyimide to cause a condensation reaction between the ketone group in the adhesive polyimide and the primary amino group of the crosslinking amino compound. This condensation reaction causes the resin solution to harden into a hardened product. In this case, the amount of the crosslinking amino compound added can be 0.004 mol to 1.5 mol, preferably 0.005 mol to 1.2 mol, more preferably 0.03 mol to 0.9 mol, and most preferably 0.04 mol to 0.6 mol of primary amino group per 1 mol of ketone group. When the amount of crosslinking amino compound added is such that the total number of primary amino groups per mole of ketone groups is less than 0.004 moles, crosslinking by the crosslinking amino compound is insufficient, and heat resistance after curing tends to be difficult to exhibit. When the amount of crosslinking amino compound added exceeds 1.5 moles, unreacted crosslinking amino compound acts as a thermoplasticizer, tending to reduce the heat resistance of the adhesive layer.
[0084] The conditions of the condensation reaction for forming crosslinks are not particularly limited as long as the ketone group in the adhesive polyimide reacts with the primary amino group of the amino compound for forming crosslinks to form an imine bond (C=N bond). The temperature of the heat condensation is preferably within the range of, for example, 120 to 220°C, more preferably within the range of 140 to 200°C, for the purpose of releasing water produced by condensation out of the system, or for the purpose of simplifying the condensation step when the heat condensation reaction is carried out subsequently to the synthesis of the adhesive polyimide. The reaction time is preferably about 30 minutes to 24 hours. The end point of the reaction can be determined by measuring the infrared absorption spectrum using, for example, a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1670 cm. -1 The decrease or disappearance of the absorption peak due to the ketone group in the polyimide resin near 1635 cm -1 This can be confirmed by the appearance of an absorption peak derived from a nearby imine group.
[0085] The thermal condensation of the ketone group of the adhesive polyimide with the primary amino group of the crosslinking amino compound can be carried out, for example, by the following method: (1) A method in which, following the synthesis (imidization) of adhesive polyimide, an amino compound for crosslinking is added and heated; (2) A method in which an excess amount of an amino compound is charged in advance as a diamine component, and following the synthesis (imidization) of an adhesive polyimide, the remaining amino compound that is not involved in imidization or amidation is used as an amino compound for crosslinking and heated together with the adhesive polyimide; Or, (3) A method in which the adhesive polyimide composition containing the above-mentioned crosslinking amino compound is processed into a predetermined shape (for example, after being applied to a substrate or formed into a film), and then heated; This can be done by, etc.
[0086] In the above description, an example of a crosslinked polyimide having a crosslinked structure formed by the formation of an imine bond has been given in order to impart heat resistance to the adhesive polyimide. However, the present invention is not limited to this example. As a method for curing the polyimide, it is also possible to mix and cure the polyimide with a compound having an unsaturated bond, such as an epoxy resin, an epoxy resin curing agent, maleimide, an activated ester resin, or a resin having a styrene skeleton.
[0087] In the adhesive polyimide, the content of carbon atoms derived from 6-membered aromatic rings (excluding carbon atoms of 6-membered aromatic rings derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide is preferably within the range of 12 to 40% by weight, more preferably within the range of 17 to 38% by weight, and even more preferably within the range of 20 to 30% by weight. The content of carbon atoms derived from 6-membered aromatic rings means the content of aromatic rings contained in the adhesive polyimide (aromatic ring concentration). By setting the content of carbon atoms derived from 6-membered aromatic rings within the range of 12 to 40% by weight, the molecular motion is restricted by the interaction between aromatic rings in the polyimide, and the effect of reducing the dielectric loss tangent is exhibited. If the content of carbon atoms derived from 6-membered aromatic rings is less than 12% by weight, the motion of the molecular chain of the polyimide cannot be suppressed, and the dielectric loss tangent becomes high. If the content of carbon atoms derived from 6-membered aromatic rings exceeds 40% by weight, the polarity of the molecule becomes large, and the dielectric loss tangent becomes high.
[0088] Aromatic rings such as benzene rings vibrate at high frequencies and increase heat loss. Therefore, as a general trend, the dielectric loss tangent increases as the aromatic ring concentration in polyimide increases. However, in adhesive polyimides, if the aromatic ring concentration is within the range of 12 to 40% by weight, the dielectric loss tangent does not increase even if the aromatic ring concentration increases, and rather, the dielectric loss tangent tends to decrease up to a certain aromatic ring concentration. The reason for this behavior is not yet clear, but since adhesive polyimides are made from a dimer diamine composition, they have a relatively low aromatic ring concentration compared to polyimides made from only aromatic diamines, and it is speculated that if the concentration of aromatic rings is gradually increased from a state in which the aromatic ring concentration is low, the molecular movement is restricted by the interaction between the aromatic rings, and the dielectric loss tangent is suppressed low. It is considered that a sufficiently low dielectric loss tangent can be maintained regardless of the increase in frequency until the aromatic ring concentration reaches 40% by weight.
[0089] The adhesive polyimide preferably has a weight average molecular weight (Mw) in the range of 10,000 to 200,000, more preferably in the range of 10,000 to 60,000. If the Mw of the adhesive polyimide is less than 10,000, the dielectric constant and dielectric loss tangent tend to increase due to an increase in highly polar end groups in the polyimide molecular chain, but if the Mw is 10,000 or more, the increase in highly polar end groups is suppressed, and the increase in the dielectric constant and dielectric loss tangent can be suppressed. On the other hand, if the Mw exceeds 200,000, the viscosity becomes high when made into a varnish, the handling property decreases, and thickness unevenness tends to occur during coating. The Mw of the adhesive polyimide is more preferably in the range of 15,000 to 60,000, and most preferably in the range of 18,000 to 50,000. If Mw is less than 15,000, the dielectric constant and dielectric loss tangent may tend to increase due to an increase in the number of highly polar acid ends in the polyimide molecular chain, whereas if Mw is more than 60,000, the molecular chain length becomes too long, making it difficult to achieve the effect of introducing an alicyclic diamine or aromatic diamine, and the dielectric constant and dielectric loss tangent may tend to increase.
[0090] The adhesive polyimide preferably has a ratio (Mw / Mn) of Mw to number average molecular weight (Mn) in the range of 1.5 to 2.5, more preferably 1.8 to 2.0. The ratio Mw / Mn represents the degree of polydispersity, and the adhesive polyimide preferably has a ratio Mw / Mn of 1.5 or more. Even if Mn is about the same, the higher the degree of dispersion, the higher the frequency of high molecular weight bodies, which increases the suppression of movement due to molecular entanglement, thereby achieving low dielectric tangent and improved tear strength. In addition, since Mn represents the number of terminals of the polyimide chain more directly than Mw, by making the ratio Mw / Mn 2.5 or less and balancing with Mn while ensuring a certain degree of dispersion, it is possible to suppress the increase of highly polar terminals in the polyimide molecular chain and suppress the increase in the relative dielectric constant and dielectric tangent. Mn can be controlled by increasing the content of dimer diamine in the dimer diamine composition (i.e., reducing the trimer component and monomer component), which is thought to suppress the spread of the molecular weight of the adhesive polyimide and also contribute to improving the frequency dependency.
[0091] The adhesive polyimide can be used in the form of a resin composition. For example, the adhesive polyimide can be used in the form of a resin composition comprising the following components (A) and (B): (A) an adhesive polyimide having a ketone group; and (B) a crosslinking agent having a functional group that undergoes a nucleophilic addition reaction with the ketone group; The polyimide composition may be in the form of a polyimide composition containing the component (B). Here, the crosslinking agent of the component (B) may be the above-mentioned amino compound for crosslinking.
[0092] The polyimide composition preferably contains an adhesive polyimide as the main component of the resin component, more preferably 70% by weight or more of the resin component, even more preferably 90% by weight or more of the resin component, and most preferably the entire resin component. The main component of the resin component means a component contained in an amount of more than 50% by weight of the total resin component. The polyimide composition may contain the (B) component so that the functional group is in the range of 0.04 to 0.50 mol in total, preferably 0.04 to 0.40 mol, more preferably 0.06 to 0.30 mol, per mol of ketone group in the (A) component. If the functional group of the crosslinking agent is less than 0.04 mol in total per mol of ketone group, crosslinking does not proceed sufficiently, and heat resistance after curing tends to be difficult to be exhibited. On the other hand, if it exceeds 0.5 mol, the dielectric loss tangent tends to increase. This is presumably because the mobility of the polyimide molecular chain is restricted by the excess crosslinking agent, inhibiting the formation of an ordered structure of the molecular chain effective for suppressing the dielectric loss tangent during curing. Furthermore, if the amount of crosslinking agent is too large, the unreacted crosslinking agent acts as a thermoplasticizer, tending to reduce the heat resistance of the adhesive layer.
[0093] The polyimide composition forms crosslinks by a nucleophilic addition reaction between the ketone groups in the ketone group-containing polyimide and the functional groups of the crosslinking agent, resulting in a crosslinked polyimide, which is a cured product. The conditions of the nucleophilic addition reaction for forming crosslinks are not particularly limited and can be selected according to the type of crosslinking agent. For example, when the primary amino group of the crosslinking amino compound is reacted with the ketone group in the ketone group-containing polyimide, an imine bond (C=N bond) is generated by a condensation reaction due to heating, and a crosslinked structure is formed.
[0094] In addition, since the adhesive polyimide is soluble in a solvent, the polyimide composition can be used in a form containing a solvent. The solvent is not particularly limited as long as it can dissolve the adhesive polyimide, and examples thereof include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexane, dioxane, tetrahydrofuran, diglyme, triglyme, methanol, ethanol, benzyl alcohol, cresol, and acetone. Two or more of these solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination.
[0095] In the polyimide composition, the blending ratio of the adhesive polyimide and the solvent is not particularly limited as long as the viscosity of the composition can be maintained to a level that allows coating. The viscosity of the polyimide composition is preferably within a range of, for example, 500 mPa·s to 100,000 mPa·s. If it is outside this range, defects such as uneven thickness and streaks are likely to occur in the resin film during coating.
[0096] The polyimide composition may contain, as appropriate, optional components, such as a plasticizer, another curable resin component such as an epoxy resin, a curing agent, a curing accelerator, an organic filler, an inorganic filler, a coupling agent, and a flame retardant, within the scope of not impairing the effects of the invention.
[0097] [Resin film] The resin film according to the present embodiment is obtained by processing the adhesive polyimide or crosslinked polyimide into a film. The resin film is not particularly limited as long as it contains the adhesive polyimide or crosslinked polyimide as the main component of the resin component, preferably 60% by weight or more of the resin component, more preferably 90% by weight or more of the resin component, and most preferably the entire resin component. The main component of the resin component means a component contained in an amount of more than 50% by weight of the total resin component. The resin film may be a film (sheet) made of adhesive polyimide or crosslinked polyimide, or may be laminated on a resin base material such as an inorganic material such as copper foil or glass plate, or a polyimide film, polyamide film, or polyester film. The resin film may be appropriately blended with optional components such as plasticizers, other curable resin components such as epoxy resins, curing agents, curing accelerators, organic fillers, inorganic fillers, coupling agents, and flame retardants.
[0098] (Dielectric tangent) The resin film of the present embodiment has a dielectric loss tangent (Tanδ1) at 10 GHz and a dielectric loss tangent (Tanδ2) at 28 GHz, both of which are less than 0.0025 when measured by a split cylinder resonator (SCDR) after 24 hours of humidity conditioning under constant temperature and humidity conditions (normal state) of 23°C and 50% RH. If the dielectric loss tangent (Tanδ1 and Tanδ2) exceeds the above values, it will lead to an increase in dielectric loss when applied to a circuit board, and problems such as loss of electrical signals on the transmission path of high-frequency signals will easily occur. By making the dielectric loss tangent (Tanδ1 and Tanδ2) less than 0.0025, the dielectric loss during high-frequency signal transmission can be effectively reduced. Here, a dielectric loss tangent (Tanδ1) at 10 GHz of less than 0.0025 means that the transmission loss in the frequency band for Sub6 applications can be effectively reduced. In addition, the dielectric loss tangent (Tan δ2) at 28 GHz being less than 0.0025 means that the transmission loss can be effectively reduced in frequency bands from Sub6 to over 10 GHz, including millimeter waves.
[0099] In addition, the resin film of the present embodiment has a ratio of Tan δ2 to Tan δ1 (Tan δ2 / Tan δ1) of 0.5 to 1.0, preferably 0.6 to 1.0, more preferably 0.7 to 1.0. The ratio (Tan δ2 / Tan δ1) is an index of frequency dependency, and being 0.5 to 1.0 means that even if the frequency increases in the frequency band of 10 to 28 GHz, the dielectric tangent does not increase, but remains the same, or even decreases. Therefore, the loss during signal transmission of 10 GHz or more can be effectively reduced, which is a suitable property for application to transmission circuits of high-frequency signals from Sub6 to millimeter waves. If the ratio (Tan δ2 / Tan δ1) is less than 0.5, the variation due to frequency becomes large, making it difficult to use it as a material compatible with a wide frequency band, and if it exceeds 1.0, the transmission loss increases with increasing frequency, which is not preferable.
[0100] In addition, the resin film of the present embodiment preferably has an absolute value of the difference between Tan δ1 and Tan δ2 of 0.0010 or less. If this absolute value exceeds 0.0010, the variation due to frequency becomes large, making it difficult to use as a material compatible with a wide frequency band from Sub6 to millimeter waves. Therefore, the absolute value of the difference between Tan δ1 and Tan δ2 is more preferably 0.00060 or less, and most preferably 0.00040 or less. The absolute value of the difference between Tan δ1 and Tan δ2 means both |Tan δ1-Tan δ2| or |Tan δ2-Tan δ1|.
[0101] In addition, the resin film of the present embodiment preferably has a dielectric loss tangent (Tan δ3) of less than 0.0025 at 40 GHz measured by a split cylinder resonator (SCDR) after 24 hours of humidity conditioning under constant temperature and humidity conditions (normal state) of 23°C and 50% RH. If the dielectric loss tangent (Tan δ3) exceeds the above value, it will lead to an increase in dielectric loss when applied to a circuit board, and problems such as loss of electrical signals on the transmission path of high-frequency signals will easily occur. By making the dielectric loss tangent (Tan δ3) less than 0.0025, the dielectric loss during high-frequency signal transmission can be effectively reduced. In particular, a dielectric loss tangent (Tan δ3) of less than 0.0025 at 40 GHz means that the transmission loss in frequency bands including millimeter waves can be effectively reduced.
[0102] In addition, the resin film of the present embodiment has a ratio of Tan δ3 to Tan δ1 (Tan δ3 / Tan δ1) of 0.5 to 1.0, preferably 0.6 to 1.0, more preferably 0.7 to 1.0. The ratio (Tan δ3 / Tan δ1) is an index of frequency dependency, and being 0.5 to 1.0 means that even if the frequency increases in the frequency band of 10 to 40 GHz, the dielectric tangent does not increase, but remains the same or even decreases. Therefore, the loss during signal transmission of 10 GHz or more can be effectively reduced, which is a suitable property for application to transmission circuits of high-frequency signals from Sub6 to millimeter waves. Note that if the ratio (Tan δ3 / Tan δ1) is less than 0.5, the variation due to frequency becomes large, making it difficult to use it as a material compatible with a wide frequency band, and if it exceeds 1.0, the transmission loss increases with increasing frequency, which is not preferable.
[0103] In addition, the resin film of the present embodiment preferably has an absolute value of the difference between Tan δ1 and Tan δ3 less than 0.0011. If this absolute value is 0.0011 or more, the variation due to frequency becomes large, making it difficult to use as a material compatible with a wide frequency band from Sub6 to millimeter waves. Therefore, the absolute value of the difference between Tan δ1 and Tan δ3 is more preferably 0.00070 or less, and most preferably 0.00045 or less. The absolute value of the difference between Tan δ1 and Tan δ3 means both |Tan δ1-Tan δ3| or |Tan δ3-Tan δ1|.
[0104] (Dielectric constant) The resin film of the present embodiment has a relative dielectric constant (ε) of 3.0 or less, preferably 2.7 or less, in the frequency band of 10 GHz to 40 GHz measured by a split cylinder resonator (SCDR) after 24 hours of humidity conditioning under constant temperature and humidity conditions (normal state) of 23°C and 50% RH. If the relative dielectric constant (ε) exceeds the above value, it leads to an increase in dielectric loss when applied to a circuit board, and is likely to cause inconveniences such as loss of electrical signals on the transmission path of high-frequency signals in the GHz band (e.g., 1 to 50 GHz).
[0105] (glass transition temperature) The resin film of the present embodiment preferably has a glass transition temperature (Tg) of 250° C. or less, and more preferably in the range of 40° C. to 200° C. If the resin film has a Tg of 250° C. or less, thermocompression bonding at a low temperature is possible, and the internal stress generated during lamination can be alleviated, and dimensional change after circuit processing can be suppressed. If the resin film has a Tg of more than 250° C., the bonding temperature becomes high, and there is a risk of impairing dimensional stability after circuit processing.
[0106] (tensile modulus) The tensile modulus of the resin film is preferably 3000 MPa or less, preferably in the range of 100 MPa to 2500 MPa, more preferably in the range of 200 MPa to 2000 MPa. If the tensile modulus is less than 100 MPa, the film may easily wrinkle, and handling properties may be deteriorated due to air entrapment during lamination. If the tensile modulus exceeds 3000 MPa, warping may occur or dimensional stability may decrease when the substrate and the resin film are laminated. By setting the tensile modulus to the above range, a laminate having good handling properties, suppressing warping and excellent dimensional stability can be obtained.
[0107] (Thickness) Although there is no particular limit to the thickness of the resin film of the present embodiment, for example, in the case of making it a self-supporting film, the thickness is preferably in the range of 5 μm to 125 μm, and more preferably in the range of 8 μm to 100 μm. If the thickness of the resin film is less than 5 μm, there is a risk of problems such as wrinkles occurring during transportation in the production of the resin film, while if the thickness of the resin film exceeds 125 μm, there is a risk of a decrease in productivity of the resin film. On the other hand, when the resin film of the present embodiment is used in a state of being laminated with a substrate or an arbitrary resin layer, the lower limit of the thickness may be, for example, 0.1 μm or more.
[0108] The use of the resin film of the present embodiment is not particularly limited, but is preferably a high-frequency transmission board in the GHz band (for example, 1 to 50 GHz), and examples include a transmission circuit board used in 5G and a millimeter-wave transmission board used in sensors in automobiles, etc. Liquid crystal polymers (LCPs) are sometimes used for high-frequency transmission FPCs, but LCPs have a tendency for the dielectric tangent to increase with an increase in the frequency of the signal (frequency dependence), and aromatic polyimides also show frequency dependence in which the dielectric tangent increases with an increase in frequency. Some conventional materials have a dielectric tangent that decreases with an increase in frequency, but in that case, the dielectric tangent in the GHz band is 0.003 or more, and is not suitable for transmitting high-frequency signals. In contrast, the resin film of the present embodiment has an excellent feature (frequency independence) that the dielectric tangent is constant or decreases in the opposite direction even when the frequency increases, despite the fact that the dielectric tangent (Tan δ1, Tan δ2, and Tan δ3) is very low at less than 0.0025 as described above, and is therefore particularly suitable for use in the GHz band.
[0109] A preferred embodiment of the resin film of the present invention is an adhesive film.
[0110] The method for producing the resin film of the present embodiment is not particularly limited, but the following methods [1] to [3] can be exemplified. [1] A method in which an adhesive polyimide is applied in a solution state (e.g., in the form of a polyimide composition) to any substrate to form a coating film, which is then dried at a temperature of, for example, 80 to 180°C to form a film, and then peeled off from the substrate as necessary. [2] A method in which a solution of polyamic acid, which is a precursor of adhesive polyimide, is applied to any substrate, dried, and then imidized to form a film, which is then peeled off from the substrate as necessary. [3] A method in which a solution of polyamic acid, a precursor of adhesive polyimide, is applied to any substrate and dried, and then the polyamic acid gel film is peeled off from the substrate and imidized to form a resin film. The method for applying the adhesive polyimide solution (or polyamic acid solution) onto the substrate is not particularly limited, and it is possible to apply it using, for example, a coater such as a comma, die, knife or lip coater.
[0111] Next, specific examples of laminates, metal-clad laminates, circuit boards, and multilayer circuit boards, which are preferred embodiments to which a resin film is applied, will be described.
[0112] [Laminate] As shown in FIG. 1, the laminate 100 according to an embodiment of the present invention has a substrate 10 and an adhesive layer 20 laminated on at least one surface of the substrate 10, and the adhesive layer 20 is made of the above-mentioned resin film. The laminate 100 may include any layer other than the above. Examples of the substrate 10 in the laminate 100 include substrates made of inorganic materials such as copper foil and glass plate, and substrates made of resin materials such as polyimide-based films, polyamide-based films, and polyester-based films. The laminate 100 can be manufactured according to any one of the above-mentioned resin film manufacturing methods [1] to [3], except that the laminate 100 is not peeled off from the substrate 10. The laminate 100 may also be manufactured by separately preparing the substrate 10 and the resin film and laminating them together. Preferred embodiments of the laminate 100 include a coverlay film, a copper foil with resin, and the like.
[0113] (Coverlay film) Although not shown, the coverlay film, which is one embodiment of the laminate 100, has a coverlay film material layer as a substrate 10 and an adhesive layer 20 laminated on one side of the coverlay film material layer, the adhesive layer 20 being made of the above-mentioned resin film. The coverlay film may include any layer other than those described above.
[0114] The material of the coverlay film material layer is not particularly limited, but for example, polyimide-based films such as polyimide resins, polyetherimide resins, and polyamideimide resins, polyamide-based films, and polyester-based films can be used. Among these, it is preferable to use polyimide-based films with excellent heat resistance. In addition, the coverlay film material layer can contain a black pigment in order to effectively exhibit light-shielding properties, concealing properties, design properties, and the like, and can also contain optional components such as matte pigments that suppress the gloss of the surface, within a range that does not impair the effect of improving the dielectric properties.
[0115] The thickness of the coverlay film material layer is not particularly limited, but is preferably within the range of, for example, 5 μm or more and 100 μm or less. The thickness of the adhesive layer 20 is not particularly limited, but is preferably within the range of, for example, 10 μm or more and 75 μm or less.
[0116] The coverlay film of the present embodiment can be produced by the method exemplified below. First, as a first method, polyimide that will become the adhesive layer 20 is applied in a solution state (for example, a varnish state containing a solvent is preferable, and a polyimide composition is preferable) to one side of a film material layer for the coverlay, and then the adhesive layer 20 is formed by drying at a temperature of, for example, 80 to 180°C, thereby forming a coverlay film having a film material layer for the coverlay and the adhesive layer 20.
[0117] As a second method, polyimide for adhesive layer 20 is applied in a solution state (for example, a varnish containing a solvent is preferable, and a polyimide composition is preferable) onto any substrate, dried at a temperature of, for example, 80 to 180°C, and then peeled off to form a resin film for adhesive layer 20, and this resin film is thermocompression bonded to a film material layer for the coverlay at a temperature of, for example, 60 to 220°C to form a coverlay film.
[0118] (Copper foil with resin) Although not shown, a resin-coated copper foil, which is another embodiment of the laminate 100, is obtained by laminating an adhesive layer 20 on at least one side of a copper foil as a substrate 10, and the adhesive layer 20 is made of the above-mentioned resin film. The resin-coated copper foil of this embodiment may include any layer other than those described above.
[0119] The thickness of the adhesive layer 20 in the resin-coated copper foil is preferably within the range of 0.1 to 125 μm, and more preferably within the range of 0.3 to 100 μm. If the thickness of the adhesive layer 20 is less than the above lower limit, problems such as insufficient adhesion may occur. On the other hand, if the thickness of the adhesive layer 20 exceeds the above upper limit, problems such as reduced dimensional stability may occur. In addition, from the viewpoint of lowering the dielectric constant and the dielectric loss tangent, the thickness of the adhesive layer 20 is preferably 3 μm or more.
[0120] The material of the copper foil in the resin-coated copper foil is preferably one mainly composed of copper or a copper alloy. The thickness of the copper foil is preferably 35 μm or less, more preferably in the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the copper foil is preferably 5 μm. The copper foil may be a rolled copper foil or an electrolytic copper foil. In addition, a commercially available copper foil can be used as the copper foil.
[0121] The resin-attached copper foil may be prepared, for example, by forming a seed layer by sputtering a metal on a resin film, and then forming a copper layer by, for example, copper plating, or by laminating a resin film and a copper foil by a method such as thermocompression bonding. Furthermore, the resin-attached copper foil may be prepared by casting a coating solution of an adhesive polyimide or a precursor thereof on the copper foil, drying the coating film, and then carrying out the necessary heat treatment to form the adhesive layer 20 on the copper foil.
[0122] [Metal-clad laminate] (First aspect) The metal-clad laminate according to one embodiment of the present invention includes an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, at least one of the insulating resin layers being made of the above-mentioned resin film. Note that the metal-clad laminate according to this embodiment may include any layer other than those described above.
[0123] (Second aspect) A metal-clad laminate according to another embodiment of the present invention is a so-called three-layer metal-clad laminate 101 including an insulating resin layer 30, an adhesive layer 20 laminated on at least one surface of the insulating resin layer 30, and a metal layer M laminated on the insulating resin layer 30 via the adhesive layer 20, as shown in FIG. 2, and the adhesive layer 20 is made of the above-mentioned resin film. The three-layer metal-clad laminate 101 may include any layer other than the above. The three-layer metal-clad laminate 101 may have the adhesive layer 20 on one or both surfaces of the insulating resin layer 30, and the metal layer M may have the adhesive layer 20 on one or both surfaces of the insulating resin layer 30. In other words, the three-layer metal-clad laminate 101 may be a single-sided metal-clad laminate or a double-sided metal-clad laminate. A single-sided or double-sided FPC can be manufactured by performing wiring circuit processing such as etching the metal layer M of the three-layer metal-clad laminate 101.
[0124] The insulating resin layer 30 in the three-layer metal-clad laminate 101 is not particularly limited as long as it is made of a resin having electrical insulation properties, and examples thereof include polyimide, epoxy resin, phenolic resin, polyethylene, polypropylene, polytetrafluoroethylene, silicone, ETFE, etc., but is preferably made of polyimide. The polyimide layer constituting the insulating resin layer 30 may be a single layer or multiple layers, but preferably includes a non-thermoplastic polyimide layer.
[0125] The thickness of the insulating resin layer 30 in the three-layer metal-clad laminate 101 is preferably within a range of, for example, 1 to 125 μm, and more preferably within a range of 5 to 100 μm. If the thickness of the insulating resin layer 30 is less than the above lower limit, problems such as inability to ensure sufficient electrical insulation may occur. On the other hand, if the thickness of the insulating resin layer 30 exceeds the above upper limit, problems such as the metal-clad laminate being more likely to warp may occur.
[0126] The thickness of the adhesive layer 20 in the three-layer metal-clad laminate 101 is preferably within a range of, for example, 0.1 to 125 μm, and more preferably within a range of 0.3 to 100 μm. In the three-layer metal-clad laminate 101 of the present embodiment, if the thickness of the adhesive layer 20 is less than the above lower limit, problems such as insufficient adhesion may occur. On the other hand, if the thickness of the adhesive layer 20 exceeds the above upper limit, problems such as reduced dimensional stability may occur. In addition, from the viewpoint of reducing the dielectric constant and dielectric loss tangent of the entire insulating layer, which is a laminate of the insulating resin layer 30 and the adhesive layer 20, the thickness of the adhesive layer 20 is preferably 3 μm or more.
[0127] Moreover, the ratio of the thickness of the insulating resin layer 30 to the thickness of the adhesive layer 20 (thickness of the insulating resin layer 30 / thickness of the adhesive layer 20) is preferably within a range of, for example, 0.1 to 3.0, and more preferably within a range of 0.15 to 2.0. By setting such a ratio, it is possible to suppress warping of the three-layer metal-clad laminate 101. Moreover, the insulating resin layer 30 may contain a filler as necessary. Examples of the filler include silicon dioxide, aluminum oxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, and metal salts of organic phosphinic acid. These can be used alone or in combination of two or more kinds.
[0128] (Third aspect) A metal-clad laminate according to still another embodiment of the present invention is, for example, as shown in Fig. 3, a laminated type metal-clad laminate 102 formed by laminating at least two single-sided metal-clad laminates via an adhesive layer 20. The laminated type metal-clad laminate 102 comprises a first single-sided metal-clad laminate 41, a second single-sided metal-clad laminate 42, and an adhesive layer 20 laminated between the first single-sided metal-clad laminate 41 and the second single-sided metal-clad laminate 42, and the adhesive layer 20 is made of the above-mentioned resin film. Here, the first single-sided metal-clad laminate 41 has a first metal layer M1 and a first insulating resin layer 31 laminated on at least one side of the first metal layer M1. The second single-sided metal-clad laminate 42 has a second metal layer M2 and a second insulating resin layer 32 laminated on at least one side of the second metal layer M2. The adhesive layer 20 is disposed so as to abut against the first insulating resin layer 31 and the second insulating resin layer 32. The laminated metal-clad laminate 102 may include any layer other than those described above.
[0129] The first insulating resin layer 31 and the second insulating resin layer 32 in the laminated metal-clad laminate 102 may have the same configuration as the insulating resin layer 30 in the three-layer metal-clad laminate 101 of the second embodiment. The laminated metal-clad laminate 102 can be manufactured by preparing a first single-sided metal-clad laminate 41 and a second single-sided metal-clad laminate 42, and placing a resin film between the first insulating resin layer 31 and the second insulating resin layer 32 and laminating them together.
[0130] (Fourth aspect) 4, a metal-clad laminate according to still another embodiment of the present invention is a metal-clad laminate 103 with an adhesive layer, which includes a single-sided metal-clad laminate having an insulating resin layer 33 and a metal layer M laminated on one side of the insulating resin layer 33, and an adhesive layer 20 laminated on the other side of the insulating resin layer 33, and the adhesive layer 20 is made of the above-mentioned resin film. Note that the metal-clad laminate 103 with an adhesive layer may include any layer other than those described above. The insulating resin layer 33 in the adhesive layer-attached metal-clad laminate 103 may have a configuration similar to that of the insulating resin layer 30 in the three-layer metal-clad laminate 101 of the second embodiment. The adhesive layer-attached metal-clad laminate 103 can be produced by preparing a single-sided metal-clad laminate having an insulating resin layer 33 and a metal layer M, and laminating a resin film to the insulating resin layer 33 side.
[0131] In the metal-clad laminate of any of the first to fourth exemplary embodiments above, the material of the metal layer M (including the first metal layer M1 and the second metal layer M2, the same applies below) is not particularly limited, and examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among these, copper or a copper alloy is particularly preferred. The material of the wiring layer in the circuit board described below is also the same as that of the metal layer M.
[0132] The thickness of the metal layer M is not particularly limited, but when a metal foil such as copper foil is used, it is preferably 35 μm or less, more preferably in the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the metal foil is preferably 5 μm. When copper foil is used, it may be rolled copper foil or electrolytic copper foil. In addition, commercially available copper foil may be used as the copper foil. In addition, the metal foil may be subjected to a surface treatment such as siding, aluminum alcoholate, aluminum chelate, silane coupling agent, etc., for the purpose of, for example, rust prevention treatment or improvement of adhesive strength.
[0133] [Circuit board] (First aspect) The circuit board according to the embodiment of the present invention is obtained by wiring the metal layer of the metal-clad laminate according to any of the above embodiments. One or more metal layers of the metal-clad laminate are patterned by a conventional method to form a wiring layer (conductor circuit layer), thereby manufacturing a circuit board such as an FPC. The circuit board may include a coverlay film that covers the wiring layer.
[0134] (Second aspect) 5, a circuit board 200 according to another embodiment of the present invention includes a first base material 11, a wiring layer 50 laminated on at least one surface of the first base material 11, and an adhesive layer 20 laminated on the surface of the first base material 11 facing the wiring layer 50 so as to cover the wiring layer 50, the adhesive layer 20 being made of the above-mentioned resin film. Note that the circuit board 200 may include any layer other than those described above. The first base material 11 in the circuit board 200 may have the same configuration as the insulating resin layer of the metal-clad laminate. The circuit board 200 can be manufactured by laminating a resin film to the wiring layer 50 side of a circuit board including the first base material 11 and the wiring layer 50 laminated on at least one surface of the first base material 11.
[0135] (Third aspect) As shown in FIG. 6, a circuit board 201 according to another embodiment of the present invention includes a first base material 11, a wiring layer 50 laminated on at least one surface of the first base material 11, an adhesive layer 20 laminated on the surface of the first base material 11 facing the wiring layer 50 so as to cover the wiring layer 50, and a second base material 12 laminated on the surface of the adhesive layer 20 opposite the first base material 11, and the adhesive layer 20 is made of the resin film. The circuit board 201 may include any layer other than those described above. The first base material 11 and the second base material 12 in the circuit board 201 may have the same configuration as the insulating resin layer of the metal-clad laminate. The circuit board 201 can be manufactured by bonding a second substrate 12 to the wiring layer 50 side of a circuit board having a first substrate 11 and a wiring layer 50 laminated on at least one surface of the first substrate 11 via a resin film.
[0136] (Fourth aspect) As shown in FIG. 7, the circuit board 202 according to another embodiment of the present invention includes a first base material 11, an adhesive layer 20 laminated on at least one surface of the first base material 11, a second base material 12 laminated on the surface of the adhesive layer 20 opposite the first base material 11, and wiring layers 50, 50 laminated on the surfaces of the first base material 11 and the second base material 12 opposite the adhesive layer 20, respectively, and the adhesive layer 20 is made of the above-mentioned resin film. The circuit board 202 may include any layer other than the above. The first base material 11 and the second base material 12 in the circuit board 202 may have the same configuration as the insulating resin layer of the above-mentioned metal-clad laminate. Circuit board 202 can be manufactured by preparing a first circuit board having a first substrate 11 and a wiring layer 50 laminated on at least one surface of first substrate 11, and a second circuit board having a second substrate 12 and a wiring layer 50 laminated on at least one surface of second substrate 12, and then placing a resin film between first substrate 11 of the first circuit board and second substrate 12 of the second circuit board and laminating them together.
[0137] [Multilayer circuit board] A multilayer circuit board according to an embodiment of the present invention includes a laminate in which a plurality of insulating resin layers are laminated, and one or more wiring layers embedded inside the laminate, and at least one of the plurality of insulating resin layers is formed of an adhesive layer 20 that has adhesiveness and covers the wiring layer, and the adhesive layer 20 is made of the above-mentioned resin film. Note that the multilayer circuit board of this embodiment may include any layer other than those described above. For example, as shown in FIG. 8, the multilayer circuit board 203 of the present embodiment has at least two insulating resin layers 34 and at least two wiring layers 50, and at least one of the wiring layers 50 is covered with an adhesive layer 20. The adhesive layer 20 covering the wiring layer 50 may partially cover the surface of the wiring layer 50, or may cover the entire surface of the wiring layer 50. The multilayer circuit board 203 may also have a wiring layer 50 exposed on the surface of the multilayer circuit board 203. The multilayer circuit board 203 may also have an interlayer connection electrode (via electrode) in contact with the wiring layer 50. The wiring layer 50 is formed by forming a conductor circuit in a predetermined pattern on one or both sides of the insulating resin layer 34. The conductor circuit may be patterned on the surface of the insulating resin layer 34, or may be patterned in a damascene (embedded) manner. The insulating resin layer 34 in the multilayer circuit board 203 may have the same configuration as the insulating resin layer of the metal-clad laminate.
[0138] The circuit board and multilayer circuit board of each of the above-described embodiments include the adhesive layer 20 containing adhesive polyimide, so that it is possible to reduce transmission loss even in high frequency transmission. EXAMPLES
[0139] The features of the present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to the examples. In the following examples, various measurements and evaluations are as follows, unless otherwise specified.
[0140] [Method for measuring amine value] Approximately 2 g of the dimer diamine composition is weighed into a 200-250 mL Erlenmeyer flask, and phenolphthalein is used as an indicator. A 0.1 mol / L ethanolic potassium hydroxide solution is dropped into the solution until the solution turns light pink, and the solution is dissolved in approximately 100 mL of neutralized butanol. 3-7 drops of phenolphthalein solution are added thereto, and titration is performed with 0.1 mol / L ethanolic potassium hydroxide solution while stirring until the sample solution turns light pink. Five drops of bromophenol blue solution are added thereto, and titration is performed with 0.2 mol / L hydrochloric acid / isopropanol solution while stirring until the sample solution turns yellow. The amine value is calculated according to the following formula (1). Amine value = {(V2 x C2) - (V1 x C1)} x M KOH / m (1) Here, the amine value is expressed as mg-KOH / g, and M KOH is the molecular weight of potassium hydroxide, 56.1. V and C are the volume and concentration of the solution used in the titration, respectively, and the subscripts 1 and 2 represent a 0.1 mol / L ethanolic potassium hydroxide solution and a 0.2 mol / L hydrochloric acid / isopropanol solution, respectively. Furthermore, m is the sample weight in grams.
[0141] [Measurement of weight average molecular weight (Mw) and number average molecular weight (Mn) of polyimide] The weight average molecular weight and the number average molecular weight were measured by gel permeation chromatography (HLC-8220GPC, manufactured by Tosoh Corporation). Polystyrene was used as a standard substance, and tetrahydrofuran (THF) was used as a developing solvent.
[0142] [How to calculate Cp value] The weight content of carbon atoms derived from 6-membered aromatic rings (excluding carbon atoms of 6-membered aromatic rings derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide was defined as the Cp value.
[0143] [Glass transition temperature (Tg)] The glass transition temperature (Tg) was measured using a thermomechanical analyzer (TMA: manufactured by Netsch, product name: TMA4000SA) for an adhesive film measuring 5 mm x 20 mm, at a heating rate of 5°C / min from 0°C to 300°C. The temperature at which the elongation changes during heating is defined as the glass transition temperature. Here, the term "thermoplastic polyimide" generally refers to a polyimide that can be softened by heating and solidified by cooling repeatedly, and has a clearly identifiable glass transition temperature, but in the present invention, it refers to a polyimide whose glass transition temperature can be clearly confirmed in a temperature range of 150° C. or less. From the viewpoint of thermocompression bonding at low temperatures, the thermoplastic polyimide is preferably a polyimide whose glass transition temperature can be clearly confirmed in a temperature range of 100° C. or less, and whose storage modulus at 30° C. measured using a dynamic mechanical analyzer (DMA) is 1.0×10 8 Pa or more, and the storage modulus at the glass transition temperature +30°C is 1.0 x 10 7 In contrast, the term "non-thermoplastic polyimide" refers to a polyimide that does not soften or exhibit adhesiveness even when heated, and in the present invention, the polyimide has a storage modulus of 1.0×10 at 30° C. as measured using a dynamic mechanical analyzer (DMA). 9 Pa or more, and the storage modulus at 300°C is 1.0 x 10 8 This means that it indicates Pa or higher.
[0144] [Tensile modulus] The tensile modulus was measured by the following procedure. First, a test piece (width 12.7 mm × length 127 mm) was prepared from the adhesive film using a tension tester (manufactured by Orientec Co., Ltd., product name: Tensilon). Using this test piece, a tensile test was performed at 50 mm / min to determine the tensile modulus at 25°C.
[0145] [Measurement of dielectric constant and dielectric tangent] Using a network analyzer (Keysight Technologies, product name: Network Analyzer N5290A) and a split cylinder resonator (SCDR), a certain number of resin sheets were stacked at a temperature of 23°C and a humidity of 50% to obtain an evaluation sample with a total thickness of about 100 μm. The sample was then heat-treated at a temperature of 180°C, a pressure of 2 MPa, and 1.0 hour using a small precision press machine manufactured by Kitagawa Seiki Co., Ltd. After conditioning the sample for 24 hours or more under the conditions of a temperature of 23°C and a humidity of 50%, the relative dielectric constant (ε1) and dielectric loss tangent (Tanδ1) at a frequency of 10 GHz, the relative dielectric constant (ε2) and dielectric loss tangent (Tanδ2) at a frequency of 28 GHz, and the relative dielectric constant (ε3) and dielectric loss tangent (Tanδ3) at a frequency of 40 GHz were measured. In addition, the value serving as an index of the frequency dependence of the dielectric loss tangent was calculated using the following formula. P 12 Value = Tan δ2 / Tan δ1 R 12 Value = Tan δ1 - Tan δ2 P 13 Value = Tan δ3 / Tan δ1 R 13 Value = Tan δ1-Tan δ3
[0146] [Warpage evaluation method] Warpage was evaluated by the following method. A polyimide solution or adhesive composition was applied to a 25 μm thick polyimide film (manufactured by Toray DuPont Co., Ltd., product name: Kapton 100EN) or a 12 μm thick copper foil so that the thickness after drying was 25 μm, to prepare a test specimen. In this state, the polyimide film or copper foil was placed on the bottom, and the average height of the warpage at the four corners of the test specimen was measured, with a value of 5 mm or less being rated as "good" and a value of more than 5 mm being rated as "unacceptable."
[0147] [Calculation of GPC and chromatogram area percentage] For GPC, 20 mg of the dimer diamine composition was pretreated with 200 μL of acetic anhydride, 200 μL of pyridine, and 2 mL of THF to prepare a 100 mg solution, which was then diluted with 10 mL of THF (containing 1000 ppm of cyclohexanone) to prepare a sample. The prepared sample was measured using a Tosoh Corporation product name: HLC-8220GPC under the following conditions: column: TSK-gel G2000HXL, G1000HXL, flow rate: 1 mL / min, column (oven) temperature: 40° C., injection volume: 50 μL. Cyclohexanone was used as a standard substance to correct the elution time.
[0148] In this case, the retention times were adjusted so that the peak top of the cyclohexanone main peak was at a retention time of 27 to 31 minutes, and the period from the peak start to the peak end of the cyclohexanone main peak was 2 minutes, and the peak top of the main peak excluding the cyclohexanone peak was at a retention time of 18 to 19 minutes, and the period from the peak start to the peak end of the main peak excluding the cyclohexanone peak was at a retention time of 2 minutes to 4 minutes 30 seconds, (a) Component represented by the main peak; (b) A component represented by a GPC peak detected at a time later than the minimum retention time of the main peak; (c) Components represented by GPC peaks detected at earlier retention times than the minimum value of the main peak on the earlier side; was detected.
[0149] The abbreviations used in the examples represent the following compounds. BTDA: 3,3',4,4'-benzophenonetetracarboxylic dianhydride 6FDA: 4,4'-(hexafluoroisopropylidene)diphthalic anhydride BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride DDA: aliphatic diamine having 36 carbon atoms (manufactured by Croda Japan Co., Ltd., product name: refined PRIAMINE 1074, component a: 97.9%, component b: 0.3%, component c: 1.8%, amine value: 210 mg KOH / g, mixture of dimer diamines having cyclic and chain structures) BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane BAFL: Bisaniline fluorene N-12: Dodecanedioic acid dihydrazide NMP: N-methyl-2-pyrrolidone OP935: Aluminum salt of phosphinic acid (manufactured by Clariant, trade name: Exolit OP935, aluminum diethylphosphinate, phosphorus content 23%, average particle size 2 μm) SR-3000: Phosphate ester (manufactured by Daihachi Chemical Industry Co., Ltd., product name: SR-3000, non-halogen aromatic condensed phosphate ester, phosphorus content: 7.0%) In the above DDA, the "%" of component a, component b, and component c means the area percentage of the chromatogram in GPC measurement. The molecular weight of the above DDA was calculated by the following formula. Molecular weight = 56.1 x 2 x 1000 / amine value
[0150] [Example 1] A 1000 ml separable flask was charged with 21.35 g of BTDA (0.0663 mol), 29.44 g of 6FDA (0.0663 mol), 63.72 g of DDA (0.1193 mol), 5.44 g of BAPP (0.0133 mol), 168.0 g of NMP, and 112.0 g of xylene, and mixed thoroughly at 40° C. for 1 hour to prepare a polyamic acid solution. The polyamic acid solution was heated to 190° C., heated and stirred for 5 hours, and xylene was added so that the solid content became 30% by weight to complete the imidization, resulting in a polyimide solution 1 (weight average molecular weight: 41,428, number average molecular weight: 21,924, C p ;19.90%) was prepared.
[0151] [Examples 2 to 4] Polyimide solutions 2 to 4 were prepared in the same manner as in Example 1, except that the raw material compositions shown in Table 1 were used.
[0152] [Table 1]
[0153] [Example 5] Polyimide solution 1 was applied to one side of release PET film 1 (Higashiyama Film Co., Ltd., product name: HY-S05, length x width x thickness = 200 mm x 300 mm x 25 μm), dried at 120°C for 10 minutes, and the adhesive layer was peeled off from release PET film 1 to prepare adhesive film 1 with a thickness of 25 μm. The various evaluation results of adhesive film 1 are as follows. ε1;2.5, Tanδ1;0.00141 ε2;2.5, Tanδ2;0.00132 ε3;2.5, Tanδ3;0.00128 P 12 Value = Tan δ2 / Tan δ1 = 0.94 R 12 Value = Tan δ1 - Tan δ2 = 0.00009 P 13 Value = Tan δ3 / Tan δ1 = 0.91 R 13 Value = Tan δ1-Tan δ3 = 0.00013 Tg: 46°C (thermoplastic), tensile modulus: 590MPa
[0154] [Examples 6 to 8] Adhesive films 2 to 4 were prepared in the same manner as in Example 5, except that polyimide solutions 2 to 4 were used. The evaluation results of various properties are shown in Table 2.
[0155] [Table 2]
[0156] [Example 9] 1.1 g of N-12 (0.004 mol) was mixed with 100 g of polyimide solution 4 (30 g as solid content), and diluted with 7.5 g of OP935 and 14.0 g of xylene, and further stirred for 1 hour to prepare adhesive composition 9.
[0157] The adhesive composition 9 was applied to one side of a release PET film 1 and dried at 120°C for 10 minutes to obtain a resin laminate with an adhesive layer thickness of 25 μm. The adhesive layer was then peeled off from the release PET film 1 to prepare an adhesive film 9 with a thickness of 25 μm.
[0158] The adhesive film 9 was heat-treated in a small precision press manufactured by Kitagawa Seiki Co., Ltd. under conditions of a temperature of 180° C., a pressure of 2 MPa, and 1.0 hour to prepare a resin sheet 9. The resin sheet 9 was subjected to spectrum measurement using a laser Raman spectrophotometer (manufactured by JASCO Corporation, product name: NRS-3100) to find a peak at 1575 cm -1 A peak due to cross-linking was confirmed around this point. The various evaluation results of the resin sheet 9 are as follows. ε1;2.7, Tanδ1;0.00182 ε2;2.7, Tanδ2;0.00156 ε3;2.7, Tanδ3;0.00146 P 12 Value = Tan δ2 / Tan δ1 = 0.86 R 12 Value = Tan δ1 - Tan δ2 = 0.00026 P 13 Value = Tan δ3 / Tan δ1 = 0.80 R 13 Value = Tan δ1-Tan δ3 = 0.00036 Tg: 51°C (thermoplastic), tensile modulus: 1,500MPa
[0159] [Example 10] 1.1 g of N-12 (0.004 mol) was mixed with 100 g of polyimide solution 4 (30 g as solid content), diluted with 6.0 g of SR-3000 and 14.0 g of xylene, and further stirred for 1 hour to prepare adhesive composition 10.
[0160] An adhesive film 10 was obtained and a resin sheet 10 was prepared in the same manner as in Example 9, except that the adhesive composition 10 was used. The results of various evaluations of the resin sheet 10 are as follows. ε1;2.7, Tanδ1;0.00170 ε2;2.6, Tanδ2;0.00164 ε3;2.6, Tanδ3;0.00158 P 12 Value = Tan δ2 / Tan δ1 = 0.96 R 12 Value = Tan δ1 - Tan δ2 = 0.00006 P 13 Value = Tan δ3 / Tan δ1 = 0.93 R 13 Value = Tan δ1-Tan δ3 = 0.00012 Tg: 48°C (thermoplastic), tensile modulus: 1,100MPa
[0161] Comparative Example 1 The dielectric properties of the LCP film (liquid crystal polymer film, manufactured by Kuraray Co., Ltd., product name: Vecstar CT-Z, thickness: 100 μm) are as follows. ε1;3.5, Tanδ1;0.00210 ε3;3.5, Tanδ3;0.00240 P 13 Value = Tan δ3 / Tan δ1 = 1.14 R 13 Value = Tan δ1 - Tan δ3 = -0.00030
[0162] The results of evaluation of various characteristics of Examples 9 and 10 and Comparative Example 1 are shown in Table 3.
[0163] [Table 3]
[0164] [Example 11] The adhesive composition 9 was applied to one side of an electrolytic copper foil having a thickness of 12 μm and dried at 120° C. for 30 minutes to prepare a resin-coated copper foil 11 having an adhesive layer thickness of 50 μm. The warpage state of the resin-coated copper foil 11 was “good”.
[0165] [Example 12] The adhesive composition 9 was further applied to the surface of the adhesive layer of the resin-coated copper foil 11 and dried at 120°C for 30 minutes to prepare a resin-coated copper foil 12 having an adhesive layer with a total thickness of 100 µm. The warpage state of the resin-coated copper foil 12 was "good".
[0166] [Example 13] The adhesive composition 9 was applied to one side of a polyimide film 1 (manufactured by DuPont-Toray Co., Ltd., product name: Kapton 50EN, ε1 = 3.6, tan δ1 = 0.0084, length × width × thickness = 200 mm × 300 mm × 12 μm) and dried at 120°C for 10 minutes to prepare a coverlay film 13 with an adhesive layer thickness of 25 μm. The warpage state of the coverlay film 13 was "good".
[0167] [Example 14] The release PET film 1 was laminated so as to be in contact with the adhesive layer side of the coverlay film 13, and pressure-bonded for 2 minutes at a temperature of 160°C and a pressure of 0.8 MPa using a vacuum laminator. Thereafter, the adhesive composition 9 was applied to the polyimide film 1 side of the coverlay film 13 with the release PET film 1 pressure-bonded to the adhesive layer side so as to have a thickness of 25 μm after drying, and dried at 120°C for 10 minutes. The release PET film 1 was laminated so as to be in contact with the surface on which the adhesive composition 9 was applied and dried, and pressure-bonded for 2 minutes at a temperature of 160°C and a pressure of 0.8 MPa using a vacuum laminator to prepare a polyimide adhesive laminate 14 having adhesive on both sides of the polyimide film.
[0168] [Example 15] An adhesive film 9, a polyimide film 2 (manufactured by DuPont, product name: Kapton 100-EN, thickness 25 μm, ε1 = 3.6, tan δ1 = 0.0084), an adhesive film 9 and an electrolytic copper foil of 12 μm were laminated in this order on an electrolytic copper foil of 12 μm in thickness, and the laminate was pressed using a vacuum laminator at a temperature of 160° C. and a pressure of 0.8 MPa for 2 minutes. The temperature was then increased from room temperature to 160° C., and the laminate was heat-treated at 160° C. for 4 hours to prepare a copper-clad laminate 15.
[0169] [Example 16] The coverlay film 13 was laminated onto a 12 μm thick electrolytic copper foil so that the adhesive layer side was in contact with the copper foil, and then pressed using a vacuum laminator at a temperature of 160° C. and a pressure of 0.8 MPa for 2 minutes. The temperature was then increased from room temperature to 160° C., and the film was heat-treated at 160° C. for 2 hours to prepare a copper-clad laminate 16.
[0170] [Example 17] An adhesive film 9 was laminated on a 12 μm thick rolled copper foil, and the polyimide film 1 side of the coverlay film 13 was laminated so that it was in contact with the adhesive film 9. Further, a 12 μm thick rolled copper foil was sequentially laminated on the adhesive layer side of the coverlay film 13, and the resulting laminate was pressed using a vacuum laminator at a temperature of 160° C. and a pressure of 0.8 MPa for 2 minutes. The temperature was then increased from room temperature to 160° C., and the laminate was heat-treated at 160° C. for 2 hours to prepare a copper-clad laminate 17.
[0171] [Example 18] Two sheets of resin-coated copper foil 11 were prepared, and laminated so that the adhesive layer sides of the two resin-coated copper foils 11 were in contact with a polyimide film 3 (manufactured by DuPont, product name: Kapton 200-EN, thickness 50 μm, ε1 = 3.6, tan δ1 = 0.0084). The sheets were then pressed together using a vacuum laminator at a temperature of 160°C and a pressure of 0.8 MPa for 5 minutes, after which the temperature was raised from room temperature to 160°C and heat-treated at 160°C for 4 hours to prepare a copper-clad laminate 18.
[0172] [Example 19] The adhesive composition 9 was applied to the polyimide side of a single-sided copper-clad laminate 1 (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: Espanex MC12-25-00UEM, length x width x thickness = 200 mm x 300 mm x 25 μm), and dried at 120 ° C for 30 minutes to prepare an adhesive-coated copper-clad laminate 19 with an adhesive layer thickness of 50 μm. The single-sided copper-clad laminate 1 was laminated so that the polyimide side surface of the single-sided copper-clad laminate 1 was in contact with the adhesive layer side of the adhesive-coated copper-clad laminate 19, and the laminate was pressed at a temperature of 160 ° C, a pressure of 4.0 MPa, and for 120 minutes using a small precision press to prepare a copper-clad laminate 19.
[0173] [Example 20] Two adhesive-coated copper-clad laminates 19 were laminated together with the adhesive layer sides facing each other, and pressed together using a small precision press at a temperature of 160° C. and a pressure of 4.0 MPa for 120 minutes to prepare copper-clad laminate 20.
[0174] [Example 21] An adhesive film 9 was laminated on the resin layer side of single-sided copper-clad laminate 1, and then another adhesive film 9 was laminated on top of that so that the resin layer side of single-sided copper-clad laminate 1 was in contact with the adhesive film 9. The laminate was then pressed using a small precision press at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to prepare copper-clad laminate 21.
[0175] [Example 22] The adhesive composition 9 was applied to one side of a release PET film 1, dried at 120° C. for 15 minutes, and the adhesive layer was peeled off from the release PET film 1 to obtain an adhesive film 22 with a thickness of 15 μm.
[0176] An adhesive film 22 was laminated on the resin layer side of the single-sided copper-clad laminate 1, and then another adhesive film 22 was laminated on top of that so that the resin layer side of the single-sided copper-clad laminate 1 was in contact with the adhesive film 22. The laminate was then pressed using a small precision press at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to prepare the copper-clad laminate 22.
[0177] [Example 23] A double-sided copper-clad laminate 2 (product name: ESPANEX MB12-25-00UEG, manufactured by Nippon Steel Chemical & Material Co., Ltd.) was prepared, and the copper foil on one side was subjected to circuit processing by etching to form a conductor circuit layer, thereby preparing a wiring board 2A.
[0178] The copper foil on one side of the double-sided copper-clad laminate 2 was removed by etching to prepare a copper-clad laminate 2B.
[0179] An adhesive film 22 was sandwiched between the conductive circuit layer side of the wiring board 2A and the resin layer side of the copper-clad laminate 2B, and the laminated bodies were thermocompressed at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to prepare a multilayer circuit board 23.
[0180] [Example 24] A double-sided copper-clad laminate 24 was prepared using an insulating substrate made of a liquid crystal polymer film (manufactured by Kuraray, product name: CT-Z, thickness: 50 μm, CTE: 18 ppm / K, heat distortion temperature: 300° C., ε1 = 3.40, tan δ1 = 0.0022) with 18 μm-thick electrolytic copper foil provided on both sides. The copper foil on one side was subjected to circuit processing by etching to form a conductor circuit layer, thereby preparing a wiring board 24A.
[0181] The copper foil on one side of the double-sided copper-clad laminate 24 was removed by etching to prepare a copper-clad laminate 24B.
[0182] An adhesive film 22 was sandwiched between the conductive circuit layer side of wiring board 24A and the insulating base material layer side of copper-clad laminate 24B, and the laminated sheets were thermocompression bonded at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to prepare multilayer circuit board 24.
[0183] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment, and various modifications are possible. [Explanation of symbols]
[0184] REFERENCE SIGNS LIST 10...substrate, 11...first substrate, 12...second substrate, 20...adhesive layer, 30, 33, 34...insulating resin layer, 31...first insulating resin layer, 32...second insulating resin layer, 41...first single-sided metal-clad laminate, 42...second single-sided metal-clad laminate, 50...wiring layer, M...metal layer, M1...first metal layer, M2...second metal layer, 100...laminate, 101...three-layer metal-clad laminate, 102...laminated metal-clad laminate, 103...metal-clad laminate with adhesive layer, 200, 201, 202...circuit board, 203...multilayer circuit board
Claims
1. A resin film containing polyimide as a resin component, The polyimide contains a tetracarboxylic acid residue derived from a tetracarboxylic acid anhydride component and a diamine residue derived from a diamine component, and contains 30 mol % or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine obtained by substituting two terminal carboxylic acid residues of a dimer acid with a primary aminomethyl group or an amino group, relative to the total diamine residues, and the dimer diamine composition contains the following components (a) to (c): (a) a dimer diamine in which the two terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group; (b) a monoamine compound obtained by substituting a terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group; (c) Amine compounds obtained by substituting the terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine); The component (a) is contained in an amount of 96% by area or more, the weight average molecular weight (Mw) of the polyimide is within a range of 18,000 to 50,000, and the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is within a range of 1.5 to 2.5; After 24 hours of humidity conditioning under constant temperature and humidity conditions (normal state) of 23°C and 50% RH, the dielectric loss tangent (Tanδ) at 10 GHz measured by a split cylinder resonator (SCDR) was 1 ) and dielectric tangent (Tan δ) at 28 GHz 2 ) is less than 0.0025, 1 The Tan δ 2 The ratio of (Tan δ 2 / Tan δ 1 ) is 0.5 or more and 1.0 or less.
2. The Tan δ 1 and the Tan δ 2 2. The resin film according to claim 1, wherein the absolute value of the difference between the above values is 0.0010 or less.
3. After 24 hours of humidity conditioning under constant temperature and humidity conditions (normal state) of 23°C and 50% RH, the dielectric loss tangent (Tanδ) at 40 GHz measured by a split cylinder resonator (SCDR) was 3 3. The resin film according to claim 1, wherein the ratio of Tan δ 3 to Tan δ 1 (Tan δ 3 / Tan δ 1 ) is 0.5 or more and 1.0 or less.
4. The Tan δ 1 and the Tan δ 3 The resin film according to claim 3 , wherein the absolute value of the difference is less than 0.0011.
5. A resin film as described in claim 1, in which the content of carbon atoms derived from six-membered aromatic rings (excluding carbon atoms of six-membered aromatic rings derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide is within the range of 20 to 30 weight %.
6. The resin film according to any one of claims 1 to 5, comprising a crosslinked polyimide obtained by crosslinking the polyimide through an imine bond.
7. A laminate having a substrate and an adhesive layer laminated on at least one surface of the substrate, A laminate comprising the resin film according to claim 1 , wherein the adhesive layer is made of the resin film according to claim 1 .
8. A coverlay film having a coverlay film material layer and an adhesive layer laminated on the coverlay film material layer, A coverlay film, wherein the adhesive layer is made of the resin film according to claim 1 .
9. A resin-coated copper foil in which an adhesive layer and a copper foil are laminated, A resin-coated copper foil, characterized in that the adhesive layer is made of the resin film according to any one of claims 1 to 6.
10. A metal-clad laminate having an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, 7. A metal-clad laminate, wherein at least one of the insulating resin layers is made of the resin film according to claim 1.
11. A metal-clad laminate having an insulating resin layer, an adhesive layer laminated on at least one surface of the insulating resin layer, and a metal layer laminated on the insulating resin layer via the adhesive layer, A metal-clad laminate, wherein the adhesive layer is made of the resin film according to claim 1 .
12. A first single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on at least one surface of the first metal layer; a second single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on at least one surface of the second metal layer; An adhesive layer is disposed so as to abut against the first insulating resin layer and the second insulating resin layer, and is laminated between the first single-sided metal-clad laminate and the second single-sided metal-clad laminate, A metal-clad laminate, wherein the adhesive layer is made of the resin film according to claim 1 .
13. A metal-clad laminate comprising: a single-sided metal-clad laminate having an insulating resin layer and a metal layer laminated on one side of the insulating resin layer; and an adhesive layer laminated on the other side of the insulating resin layer, wherein the adhesive layer is made of a resin film described in any one of claims 1 to 6.
14. A circuit board obtained by wiring the metal layer of the metal-clad laminate according to any one of claims 10 to 13.
15. A circuit board comprising: a first base material; a wiring layer laminated on at least one surface of the first base material; and an adhesive layer laminated on a surface of the first base material facing the wiring layer so as to cover the wiring layer, A circuit board, wherein the adhesive layer is made of the resin film according to claim 1 .
16. A circuit board comprising: a first base material; a wiring layer laminated on at least one surface of the first base material; an adhesive layer laminated on a surface of the first base material facing the wiring layer so as to cover the wiring layer; and a second base material laminated on a surface of the adhesive layer opposite to the first base material, A circuit board, wherein the adhesive layer is made of the resin film according to claim 1 .
17. A circuit board comprising: a first base material; an adhesive layer laminated on at least one surface of the first base material; a second base material laminated on a surface of the adhesive layer opposite to the first base material; and wiring layers laminated on each of the first base material and the second base material opposite to the adhesive layer, A circuit board, wherein the adhesive layer is made of the resin film according to claim 1 .
18. A multilayer circuit board comprising a laminate including a plurality of laminated insulating resin layers, and at least one wiring layer embedded in the laminate, At least one of the plurality of insulating resin layers is formed of an adhesive layer having adhesiveness and covering the wiring layer, 7. A multilayer circuit board, comprising the adhesive layer comprising the resin film according to claim 1.
Citation Information
Patent Citations
Crosslinked polyimide resin, adhesive resin composition and cured product thereof, cover lay film and circuit board
JP2013001730A
Polyimide-based adhesive
JP2017119865A
Binding agent and article bound by binding agent
JP2017137375A
Metal-clad laminate, adhesive sheet, adhesive polyimide resin composition, and circuit board
JP2018140544A
Multilayer circuit board
JP2018174286A